Prognostic Value of the Width of Invasion in pT3 Cutaneous Melanomas - Dana Antonia Țăpoi; Ancuța-Augustina Gheorghișan-Gălățeanu; Laura Maria Gosman; Adrian Vasile Dumitru; Ana Maria Ciongariu; Mariana Costache (International Journal of Translational Medicine, 2023)
Intermediate-thickness melanomas display highly variable outcomes influenced by both clinical and histopathological characteristics. This study investigates several clinicopathological prognostic factors for pT3 cutaneous melanomas, focusing on a novel parameter, the width of invasion. This is a retrospective study of 49 patients diagnosed with cutaneous melanoma between 2012 and 2018 who were followed up for at least five years. We evaluated the age, gender, tumor location, Breslow depth of invasion, width of invasion, mitotic index, the presence/absence of ulceration, regression, microsatellites, lymphovascular invasion, and perineural invasion for their association with disease progression and survival. Cox univariate analysis revealed that progression-free survival (PFS) was significantly associated with age, depth of invasion, width of invasion, lymphovascular invasion, microsatellites, and perineural invasion. Overall survival (OS) was significantly associated with age, depth of invasion, width of invasion, microsatellites, and perineural invasion. Through multivariate Cox proportional hazards regression, the only factor associated with both PFS and OS was the width of the invasion. This is one of the few studies to assess the width of invasion and we have demonstrated that this parameter could become an important prognostic factor for cutaneous melanomas.